The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1021/jp068914g
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Hydrogen Chloride with Ice Surfaces:  The Effects of Grain Size, Surface Roughness, and Surface Disorder

Abstract: Characterization of the interaction of hydrogen chloride (HCl) with polar stratospheric cloud (PSC) ice particles is essential to understanding the processes responsible for ozone depletion. The interaction of HCl with ice was studied using a coated-wall flow tube with chemical ionization mass spectrometry (CIMS) between 5 × 10 -8 and 10 -4 Torr HCl and between 186 and 223 K, including conditions recently shown to induce quasiliquid layer (QLL) formation on single crystalline ice samples. Measurements were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(111 citation statements)
references
References 111 publications
8
102
1
Order By: Relevance
“…Recently, direct laboratory evidence showed that HCl-and HNO 3 -ice interactions are highly dependent on the surface state of the ice substrate (McNeill et al, 2006(McNeill et al, , 2007Moussa et al, 2013). This pioneering work overcomes the main limitation of the above studies, by providing a link between Atmos.…”
Section: Uptake To the Disordered Interfacementioning
confidence: 93%
See 2 more Smart Citations
“…Recently, direct laboratory evidence showed that HCl-and HNO 3 -ice interactions are highly dependent on the surface state of the ice substrate (McNeill et al, 2006(McNeill et al, , 2007Moussa et al, 2013). This pioneering work overcomes the main limitation of the above studies, by providing a link between Atmos.…”
Section: Uptake To the Disordered Interfacementioning
confidence: 93%
“…3.1 and 3.2), and experimentally verified by optical reflectance (Elbaum et al, 1993), by ellipsometry (McNeill et al, 2006(McNeill et al, , 2007, and directly by partial electron yield near-edge X-ray absorption fine structure (NEXAFS) (Bluhm et al, 2002). Observations of impurity-amplified or -induced disorder at ice surfaces depend on experimental conditions, the method of experimental probing, and on the type of impurity.…”
Section: The Thickness and Effect Of Impuritiesmentioning
confidence: 96%
See 1 more Smart Citation
“…On the contrary, McNeill et al (McNeill et al 2007) concluded that the HCl adsorption and surface-to-bulk flux on polar stratospheric cloud ice particles is slightly influenced by the QLL thickness, which is allowed to vary between 1 nm and 300 nm.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, Molina and coworkers (McNeill et al 2007) studied the interaction of HCl with polar stratospheric cloud ice particles and found that the solute can induce the formation of a QLL at the characteristic temperatures of these clouds.…”
mentioning
confidence: 99%